Fuel Cell Renewable Hybrid Power Systems - Bizon, Nicu (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Climate change is becoming visible today, and so this book-through including innovative solutions and experimental research as well as state-of-the-art studies in challenging areas related to sustainable energy development based on hybrid energy systems that combine renewable energy systems with fuel cells-represents a useful resource for researchers in these fields. In this context, hydrogen fuel cell technology is one of the alternative solutions for the development of future clean energy systems. As this book presents the latest solutions, readers working in research areas related to the above are invited to read it.